2009
DOI: 10.3727/096504009789745539
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Administration of Docetaxel and Epirubicin as First-Line Treatment for Hormone-Refractory Prostate Carcinoma

Abstract: Androgen-independent prostate carcinoma (AICP) is one of the tumors that continue to respond poorly to chemotherapy. Recently, protocols based on the use of docetaxel have significantly improved survival for patients in this disease. In other types of neoplastic disease, combined therapy with taxanes and anthracycline derivatives has been shown to produce additive effects in terms of growth inhibition, and superior tolerability when associated with weekly administration schedules. These findings prompted us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Combination of DOC with other drugs has been developed for the treatment of PCA (Scheme 1). Studies have indicated that anthracyclines can enhance the inhibitory effect of DOC against PCA (Pienta, 2001;Kouroussis et al, 2005;Mackler and Pienta, 2005;Neri et al, 2005;Petrioli et al, 2007;Neri et al, 2009). Several studies have verified that the combination of DOC with DOX has a synergistic effect in the treatment of PCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of DOC with other drugs has been developed for the treatment of PCA (Scheme 1). Studies have indicated that anthracyclines can enhance the inhibitory effect of DOC against PCA (Pienta, 2001;Kouroussis et al, 2005;Mackler and Pienta, 2005;Neri et al, 2005;Petrioli et al, 2007;Neri et al, 2009). Several studies have verified that the combination of DOC with DOX has a synergistic effect in the treatment of PCA.…”
Section: Discussionmentioning
confidence: 99%
“…DOC remains the mainstream therapeutic agent for PCA treatment and is combined with other drugs, including mitoxantrone and estramustine, to treat PCA (Sinibaldi et al, 2002;Petrylak et al, 2004). Several clinical studies have demonstrated that DOC combined with anthracyclines could increase the anti-PCA effect because anthracyclines would enhance the sensitivity of the PCA cells to DOC (Pienta, 2001; Kouroussis et al, 2005;Mackler and Pienta, 2005;Neri et al, 2005;Petrioli et al, 2007;Neri et al, 2009). DOX is a kind of anthracycline that can prevent DNA remodeling (Pommier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Early stage prostate cancer requires androgen for growth and thus responds well to androgen deprivation therapy (Loblaw et al, 2007), but tumors become resistant to this therapy as disease progresses (Pilat et al, 1998;So et al, 2005;Schroder, 2008;Chi et al, 2009). Chemotherapy is the primary treatment option for late-stage prostate cancer patients, but this has limited efficacy and serious toxic side effects and the prognosis for these patients is very poor (Gomella et al, 2009;Neri et al, 2009). Therefore, there is a need for novel therapeutic approaches for treating and preventing androgen-independent prostate cancer while minimizing toxic side effects.…”
Section: Introductionmentioning
confidence: 99%